USE SOFTWARE SUPPORT FOR COMPUTER NETWORK EDUCATION - HREHOVA, Stella (Trends in education, 2013)
At the present computer networks are an integral part of work and private life. Their use is already commonplace. Graduates, however, should have at least a basic knowledge of how to computer network actually work. One of appropriate software for the visual presentation of the work of computer network, the design, management and configuration is simulation software Cisco Packet Tracer. The present paper describes how to create and control a simple computer network.
Keywords: computer net; simulation; Cisco Packet Tracer